2019
DOI: 10.1002/pits.22250
|View full text |Cite
|
Sign up to set email alerts
|

Teacher attributions for children's attention‐deficit/hyperactivity disorder behaviors predict experiences with children and with classroom behavioral management in a summer program practicum

Abstract: Elementary school teachers often implement classroom behavioral management systems to address student misbehavior. Common problems targeted by these systems are the inattentive, hyperactive, and impulsive behaviors characteristic of attention‐deficit/hyperactivity disorder (ADHD). This study examined teachers' attributions for why children display ADHD behaviors, and how such attributions affect their experiences with children in the context of interventions to manage these behaviors. Participants were 32 pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
(69 reference statements)
0
4
0
2
Order By: Relevance
“…He always does that”), tended to display harsher and more negative discipline methods—which, in turn, predicted escalation in child’s problem behaviors ( Johnston and Ohan, 2005 ). Eventually, this may result in endorsing a more punitive, harsh and criticizing educational strategy ( McAuliffe et al, 2009 ), impeding teachers from helping students to manage their behaviors (believing that it is under their control) and affecting teachers’ implementation of helpful classroom practices ( Mikami et al, 2019 ). This state of affairs often results in an escalation of undesirable behaviors; hence, these attributions are an important target for exploration, awareness and intervention.…”
Section: Discussionmentioning
confidence: 99%
“…He always does that”), tended to display harsher and more negative discipline methods—which, in turn, predicted escalation in child’s problem behaviors ( Johnston and Ohan, 2005 ). Eventually, this may result in endorsing a more punitive, harsh and criticizing educational strategy ( McAuliffe et al, 2009 ), impeding teachers from helping students to manage their behaviors (believing that it is under their control) and affecting teachers’ implementation of helpful classroom practices ( Mikami et al, 2019 ). This state of affairs often results in an escalation of undesirable behaviors; hence, these attributions are an important target for exploration, awareness and intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies reviewed, it was reported that adults tended to assess MHPs as caused by either biological factors or the family/parental environment of the child. In previous research causal beliefs regarding the etiology of MHPs have been linked to adult behaviour and decision making, and importantly to positive treatment outcomes and teacher management (Hoza et al, 2000;Mikami et al, 2019;Sawrikar et al, 2018Sawrikar et al, , 2020. Adult causal beliefs that are recovery orientated and highlight the amenability of MHPs to treatment are likely to result in better outcomes for children (Chaidez et al, 2018;Yeh et al, 2005).…”
Section: Secondary Mhlsc Outcome: Beliefs About Causesmentioning
confidence: 99%
“…Resultat från existerande forskning synliggör att relationen mellan lärare och elever med ADHD upplevs vara betydligt mer ansträngd, med högre grad av konflikter och mindre emotionell närhet än lärar-elev-relationen generellt (Mautone et al, 2011;Mikami et al, 2019). Detta är problematiskt, inte minst då det i Skolforskningsinstitutets metaöversikt (2021:02) poängteras att lärar-elev-relationen är speciellt viktig i relation till elever med svårigheter inom social interaktion, vilket är karakteristiskt för elever med ADHD (American Psychiatric Association, 2013).…”
Section: Resultatdiskussionunclassified
“…Det utagerande beteendet verkar också vara det största hindret för goda lärar-elev-relationer (Zendarski et al, 2020) och det som lärare upplever som mest utmanande i relationen till dessa elever . Beteendet tenderar dessutom att skapa negativa känslor bland lärare, något som kan resultera i disciplinära åtgärder, som i sin tur riskerar att hämma relationen ännu mer Mikami et al, 2019). Resultat från Meija och Höglund (2016) visar dock att även relationer mellan lärare och introverta elever tenderar att vara ansträngda.…”
Section: Relationen Mellan Lärare Och Elever Med Adhdunclassified